Population increase of the coffee bit, Hypothenemus hampei (Ferrari), related to the development of the coffee fruit - GUEVARA-R., ADELARDO M.; CARDENAS-M., REINALDO; MONTOYA-R., ESTHER C.; MADRIGAL-C., ALEJANDRO (Revista Colombiana de Entomología, 1995)
Due to the importance of knowing the increase in the population of the coffee berry borer, under the Colombian coffee growing conditions, related to the development of the fruit, in order to develop management programs during the critic growing stages, it was proposed to search for the relationship between the increase in population and the infestation level of the berry borer with the stage of development of the coffee fruit. Furthermore, the distribution of the berry borer in the branch and the tree and the impact of the fungus Beauveria bassiana on the berry borer under field conditions, during the development of the fruit also was studied. Eighty trees were selected at random of which 40 were used to evaluate the infestation by the borer and the natural infection by the fungus, and the other 40 were used to evaluate the number of biological stages of the borer, the mortality caused by the fungus on the adults and the dry weight of the fruits. Twelve evaluations were made fortnightly between 105 and 265 days of development of the fruit. The first eggs were found 119 days after flowering, the first larvae 113 and the first pupae after 147 days. The duration of the first generation from egg to pupa was 28 days, the average number of the borer biological stages by infected fruit increase throughout the period of fruit development. The highest increase in the infestation appeared between 133 and 220 days after flowering. The distribution of the borer infestation in the branch was higher in the first five knots from the stem out. A simple linear relation was presented between the dry weight of the fruit and the tree average infestation between 105 and 220 days after flowering. The infection and the mortality by the fungus were higher in young fruits than in ripe or over riped fruits.